Enhancing sleep quality in professional rugby players: Assessment and Intervention - Goldberg, M.; Boutin, A.; Cohn, J.; Michel, V.; Stauffer, E.; Debarnot, U. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Sleep is a crucial factor in recovery and must be integrated into athletes training plans for optimal performance and well-being1. Although professional athletes are advised to sleep for a minimum of 8 hours1, many experience shorter sleep durations or exhibit poor sleep efficiency, especially after matches or hard training cycles2,3. Recent sleep tracking observations in athletes suggest that sleep quality is altered, yet this emerging field of research requires comprehensive assessments, including objective and subjective sleep outputs. To improve sleep quality, sleep interventions have been recently tested with various modalities, including among others, sleep hygiene education and sleep strategies. Importantly, combinations of sleep interventions have been shown to improve sleep quality in young elite athletes 3,4. Therefore, across match weeks, this ecological study aimed to identify good and poor sleepers within a professional male rugby team, using both objective and subjective assessments, and to evaluate the effects of sleep interventions, including sleep hygiene education and strategies. METHODS: Forty-three male professional rugby players from national French rugby union were evaluated during two tracking and intervention match weeks using objective and subjective assessments (i.e., actimeter and Hooper questionnaire). During the first tracking week, we assessed the wake-sleep cycle of athletes who maintained their daily habits. Then, two sleep experts reported the results from the tracking phase in a group setting context and offered an educational session on sleep hygiene (30 min). Sleep experts further taught them how to practice relaxation strategies (15 min), which they could implement as needed during the post-intervention week. RESULTS: Our findings revealed that 65 % of players were considered bad sleepers. Subjective sleep quality improved between the tracking and the intervention weeks (p = 0.002, *2 = 0.22). A significant effect of the sleep hygiene intervention was also found on bedtime (p = 0.005, *2 = 0.19), which occurred earlier during the intervention week (23:25 ± 00:38 vs. 23:43 ± 00:44 during tracking). A trend towards significant increases in objective (actimetric) sleep quantity was also observed (421.3 min during tracking week vs. 433.4 min during intervention week; p = 0.07, *2 = 0.08). CONCLUSION: The first main finding revealed that a majority of professional rugby players did not sleep sufficiently, which extends previously reported results from different sports1,2,3,4. The second main finding demonstrated that sleep interventions improved sleep quality and quantity. This study offers a simple and accessible method for evaluating sleep status in team sports athletes, while providing feedback to optimize and enhance sleep quality and quantity.